166 Identifying the financial costs of anticipatory medication prescriptions: A retrospective observational study using general practitioner and community nursing records. (14th March 2023) - Morgan, Lloyd; Barclay, Stephen; Kristian, Kristian Pollock; Massou, Efthalia; Bowers, Ben
Abstract : Background: The prescribing of injectable end-of-life anticipatory medications ahead of possible need is recommended practice. The financial costs of anticipatory medication remain unknown. Aims: To identify the prescription, usage and wastage costs of anticipatory medications dispensed to patients living at home and in residential care. Design: Retrospective observational study using general practitioner and community nursing records. Data Collection: Data were collected from eleven general practitioner practices using the records of the last 30 most recent deaths per practice. Patients were aged 18+ and died between 2017–2019 from any cause except trauma, sudden death or suicide. Analysis: Anticipatory medications were prescribed to 167/329 patients, of which 164 were included in the analysis. Costs were analysed at both patient-level and drug-level using univariate and multivariate quantitative analysis. Results: Median anticipatory prescription cost was £43.17 (IQR: £38.98-£60.47, range £8.76 to £229.82). Median administration prescription cost was £2.16 (IQR: £0.00-£12.09, range £0.00 to £83.14). Median wastage was £41.47 (IQR: £29.15-£54.33, range £0.00 to £195.36). Prescription, usage and wastage costs were significantly higher for patients prescribed an anticipatory syringe driver. There were wide variations in the wastage costs of individual drugs; Haloperidol and Cyclizine contributed 49% of the total wastage costs. Conclusion: The prescription and wastage costs of anticipatory medications are higher than previously estimated but remain modest. Usage of prescriptions is lower than previously expected. There may be scope to reduce the quantity of drug vials that are routinely prescribed without adversely affecting care; prospective clinical trials are needed to explore this possibility.